Female Board Directorships and Related Party Transactions. (26th November 2021) - Usman, Muhammad; Gull, Ammar Ali; Zalata, Alaa Mansour; Wang, Fangjun; Yin, Junming
Abstract: Using a sample of Chinese firms from 2005 to 2018, we show that firms with female directors (either executive or independent) are characterized by fewer related party transactions (RPTs), particularly in state‐owned enterprises. Fewer RPTs are associated with improved subsequent operating performance and, in contrast, RPTs are associated with decreased performance for firms with no or fewer female directors, suggesting that female directors engage or allow only efficient but not opportunistic RPTs to facilitate the long‐term strategic objectives of their firms. Our findings are robust for using an alternative measure of RPTs, female board directorships and methods to mitigate potential endogeneity issues.